Nephritis in the dog associated with Leptospira canicola infection - McIntyre, W. I. M. (The University of Edinburgh, 1954)
369 dogs infected with Leptospira canicola have been examined clinically. Agglutination tests and blood urea estimations have been carried out on each case. Details of examinations are given in the appendices. The cases have been classified into two main groups, primary and secondary renal, according to the agglutination titres and these two groups have been subdivided according to the degree of nitro- gen retention as evidenced by blood urea levels. Seven primary cases were shown to have a leptospiral bacteraemia in the early stage. 46 of the primary cases were kept under observation for periods of six months to four years, during which time agglutinins against L. canicola persisted as did proteinuria and the excretion of tubular casts.

In Section 2 the renal lesions associated with L. cani- cola infection are described. The primary renal stage was characterised by an intense interstitial cellular infiltration which often localised predominantly in the corticomedullary zone. In subacute stages early fibrosis was evident but the infiltration remained the chief feature. In well established cases of chronic nephritis in the secondary stage the main lesion was extensive diffuse fibrosis with comparatively few small cellular foci remaining. Spirochaetes were sparse but were demonstrated mostly within the lumen of tubules or in the substance of a hyaline cast.

In the experimental work described in Section 3 Koch's postulates have been fulfilled by reproducing the infection in dogs and recovering the organism in pure culture from the blood and kidneys of the infected animal. The recovered organism was then passaged through another two dogs. The renal lesions produced were similar to those observed in naturally occurring primary cases although not sufficiently extensive to produce obvious malaise or nitrogen retention in the dogs infected. It is suggested that loss of virulence of the organism in vitro is the main reason for the inability to produce renal failure. Despite the lack of severity of the condition produced in the dog the cellular infiltration was characteristically mononuclear and showed a definite tendency to localise in the boundary zone. Spirochaetes were readily demonstrated in the kidneys.